Effect of Promoters on the Catalytic Activity of the Iosmerization Catalyst - A.K. Mohammed, Abdul-Halim; Gaib, Marwan; Nasief Abbass, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
The crystalline zeolite, namely faujasite type Y with SiO2/Al2O3 mole ratio of 5 was used as raw material for preparation of isomerization catalysts. A 0.5 wt % Pt/HY-zeolite catalyst was prepared by impregnation of the decationized HY-zeolite with chloroplatinic acid. The dectionized HY-zeolite was treated with HCl, HNO3 and HI promoters using different normalities and with different concentrations of Sn, Ni and Ti promoters by impregnation method to obtain acidic and metallic promoters’ catalysts, respectively. A 0.5 wt% of Pt was added to above catalysts using impregnation method. Isomerization of n-hexane was carried out at different prepared catalysts. The isomerization temperature varied from 250–325° C over weight hourly space velocity (WHSV) 1.6 h-1. The pressure and hydrogen to feed mole ratio were kept constant at 1bar and 2 mol/mol, respectively. The comparison between the above prepared catalysts shows that the total isomer yield during the process with Sn-Pt /HY- zeolite catalyst was higher than the other catalysts and, reached to 63.95% vol. A 0.5 wt% of W and Zr was added to Sn-Pt/HY-zeolite catalyst by impregnation method to obtain W and Zr co-metal promoters catalysts. Isomerization of n-hexane was investigated using W and Zr co-metal promoters catalyst at the same operating conditions and the yield of isomers reached to 81.14% vol.and 79.07%vol.,respectively.